Predicting a Correct Program in Programming by Example - Singh, Rishabh; Gulwani, Sumit (27th International Conference on Computer Aided Verification (CAV 2015), 2015)
We study the problem of efficiently predicting a correct program from a large set of programs induced from few input-output examples in Programming-by-Example (PBE) systems. This is an important problem for making PBE systems usable so that users do not need to provide too many examples to learn the desired program. We first formalize the two classes of sharing that occurs in version-space algebra (VSA) based PBE systems, namely set-based sharing and path-based sharing. We then present a supervised machine learning approach for learning a hierarchical ranking function to efficiently predict a correct program. The key observation of our learning approach is that ranking any correct program higher than all incorrect programs is sufficient for generating the correct output on new inputs, which leads to a novel loss function in the gradient descent based learning algorithm. We evaluate our ranking technique for the FlashFill PBE system on over 175 benchmarks obtained from the Excel product team and help forums. Our ranking technique works in real-time, reduces the average number of examples required for learning the desired transformation from 4.17 to 1.48, and learns the transformation from just one input-output example for 74% of the benchmarks. The ranking scheme played a pivotal role in making FlashFill usable for millions of Excel users.